PENGARUH KEMUDAHAN PENGGUNAAN KEPERCAYAAN DAN RELIGIUSITAS TERHADAP KEPUTUSAN PENGGUNAAN QRIS BANK SYARIAH PADA GENERASI Z DI KOTA SURABAYA - Muhammad Fathurrahman; A'rasy Fahrullah (STKIP Subang, 2026)
The use of Sharia Bank QRIS among Generation Z is influenced not only by technological ease but also by the users' levels of trust and religiosity. The rise in digital payment transactions highlights the need to examine the factors influencing the decision to use Sharia Bank QRIS. This study aims to analyze the influence of ease of use, trust, and religiosity on the decision to use Sharia Bank QRIS among Generation Z in Surabaya City. The research employs a quantitative approach using a purposive sampling technique with 100 respondents. Data were collected via questionnaires and analyzed using multiple linear regression. The results indicate that ease of use, trust, and religiosity have a positive and significant influence on the decision to use Sharia Bank QRIS among Generation Z in Surabaya City.